CEO Performance Measurements of PT ASTRA Otoparts Tbk 2007-2014 - Budidharma, Aditya; Nugroho, Anggoro Budi (Journal of Business and Management, 2015)
Abstract - Two important roles that have crucial role in the company in order to keep the company running First are the agents who runs the business, the performance of the agents are usually represented by the Chief Executive Officer. Chief Executive Officer or CEO for short is the head leader of a company. It is also common for some companies to call CEO as President of Director. CEO or President of Director’s job description cannot be stated as a general because each company has their own policy. Second are the shareholders or the financiers who have the capital in order for the company to keep on going. The fund that is given is represented in stocks. The relationship between agents and shareholders is concluded in the Agency Theory. Agency theory addresses the relationship where in a contract ‘one or more persons (the principal(s)) engage another person (the agent) to perform some service on their behalf which involves delegating some decision making to the agent’. Problems will arise if there is a difference of interest between the agent and shareholders. Keywords: Agency cost, stock prices, Chief Executive Officer, Shareholders